The Effect of Corporate Social Responsibility (CSR) Disclosure on Earnings Quality - Taufikurachman, Cecep; Harto, Budi; Napisah, Lilis Saidah (Jurnal Wacana Ekonomi, 2023)
Financial reports provide crucial data for decision-making processes. An increase in corporate profits is possible if more emphasis is placed on CSR. The purpose of this study is to learn how CSR reporting influences the quality of companies listed on IDX between 2017 and 2021. This study employed both descriptive and confirmatory research methods. This study focuses on the population of hotels, restaurants, and travel agencies that are registered in IDX from 2017 to 2021. "Purposive sampling" is the methodology used to choose samples for this study. Out of the initial pool of 35 companies considered, only 16 met the criteria for inclusion in the sample. Research hypotheses will be tested with a test; standard analysis, linear regression, and a deterministic koefisien will all be used in the analysis. Research results with an alpha significance level of 0.05 show that partial implementation of corporate social responsibility has a negative effect on product quality. An efficiency ratio of 2.5% indicates that CSR reports have a minimal impact on employee productivity (by comparison, other factors account for 97.5%).